Sediment provenance, sediment-dispersal systems, and major arc-magmatic events recorded in the Mexican foreland basin, North-Central and Northeastern Mexico. Issue 17 (22nd November 2019) - Juárez-Arriaga, Edgar; Lawton, Timothy F.; Ocampo-Díaz, Yam Zul E.; Stockli, Daniel F.; Solari, Luigi
ABSTRACT: The Late Cretaceous-Paleogene Mexican foreland basin (MFB), defined herein, represents the southern continuation of the late Mesozoic Cordilleran foreland basin. Sandstone petrography, new detrital-zircon (DZ) U-Pb geochronology, and paleocurrent data indicate that much of the sedimentary fill of the basin was derived from an active Late Cretaceous-Paleogene magmatic arc, termed here the Mexican Cordilleran arc, on the western continental margin of Mexico. The oldest known strata of the proximal foreland basin in the Mesa Central consist of Cenomanian-Turonian turbidites. Sampled sandstones are compositional volcanic litharenites with abundant neovolcanic grains and a dominant, approximately syndepositional DZ age group ranging 98–92 Ma that records a major magmatic event in the Mexican Cordilleran arc. Santonian-Campanian strata in the distal MFB consist of carbonate pelagites with abundant interbedded tuffs and tuffaceous sandstones. Represented by the Caracol and San Felipe formations deposited in the forebulge and back-bulge depozones, respectively, these strata form an arcuate outcrop belt 700 km in length. DZ ages ranging 85–74 Ma in the arc-derived tuffaceous strata record a second prominent magmatic event. Two principal transport mechanisms delivered volcanogenic sediment to the MFB from multiple, simultaneously active arc sources during Late Cretaceous time: (1) Cenomanian-Turonian east-directed transverse fluvial systems transported volcanic-lithic sand rich in young zircon grains; and (2) airborne ash clouds transported Santonian-Campanian zircon grains to the distal foreland basin in prevailing Late Cretaceous northwesterly winds. Axial transport of sediment derived from active arc sources, Proterozoic basement and derivative sedimentary rocks in northwestern Mexico, in addition to transverse transport from the thrust orogen itself, represents a younger sediment-routing system, modified by advance of the foreland fold-thrust belt, to the Maastrichtian-Paleogene foreland of northeastern Mexico.